The effect of the strategy (Think – Rewind – Link – Decide) on the achievement of fifth-grade students in science (Journal of the College of Basic Education, 2022)
The aim of this research is to know the effect of the strategy (think - recall - connect - make the decision) on the achievement of fifth graders in science. 2022) and the sample was chosen intentionally, and its number was (64) female students, (32) female students for the experimental group and (32) female students for the control group. After defining the scientific material, the (261) behavioral goals were formulated. As for the research tool, the researcher used the achievement test, which consisted of (30) paragraphs of the type of multiple choice. The validity of the tool was verified by presenting it to a group of arbitrators. It was applied to two survey samples, one of them was to determine the clarity of the paragraphs and the answer time, and the other was for the purpose of analyzing the test paragraphs statistically. Weeks, we used the T-test to process the data and in light of this, the results showed the following: - There is an effect of the strategy (think - recall - connect - make the decision) in the achievement in science for the fifth grade students and in favor of the experimental group, as the calculated T value reached (3,24) and the tabular value was (2).